Respuesta :

Answer:

-x - y - z  = -8   ........      (1a)

-4x + 4y +5z = 7     .....   (2a)

2x + 2x =  4   ..........       (3a)

since (3a) a is an equation solely in x make x the subject of the equation

  2 ( x + x) = 4

 divide both sides by 2

      (x + x)  = 2

            2x  = 2

              x  =  1  .......  (3b)

  substitute x in (3b) for x in (1a)

          -(1) - y - z  = -8  

    make y the subject of the equation

              -y - z  =  -8 + 1

                    -y =  -7 + z

                     y = 7 - z  ..... (1b)

 substitute y in (1b) for y in (2a) as well as the value of x ( x= 1)

        -4(1)+ 4( 7 - z ) +5z = 7

       - 4 + 28 - 4z + 5z  = 7

              -24 + z  = 7

                       z  = 7 + 24

                       z  = 31

By using (1a) solve for y

          -(1) - y - (31)= -8          

          -1  - y - 31 = -8        

                        y = -1 - 31 + 8

                        y = -24

 

∴ the solutions of the system are  x = 1 ; y = -24 ; z = 31  

Hope this helps!!!!!!!

//////////////////////////////////////////////////////////////////////////////////////////////////

Answer:Tiger Algebra gives you not only the answers, but also the complete step by step method for solving your equations 2x-y=8;2x+y=4 so that you

Step-by-step explanation: